The Structural change in the International System: From a Modified Version of Neorealism - Zandi Ziarani, Mohammad; Mirkoshesh, Amirhooshang; Razani, Ehsan (International Journal of Humanities and Education Development (IJHED), 2023)
This paper analyzes how Waltzian neorealism by some modifications can explain and predict the structural change in international system. To answer this question, we extract the main concepts of waltz definition of the system and its critics then draw the theoretical scheme to find limitation and make a synthetized modifications on waltz international system to make it applicable to study structural change in the system. Our results showed waltz theory weaknesses in the first two elements of the structure. Results also show that the international system defined by waltz needs some modifications by adding up the structure of the process to exit from the problem of having no attention to historical and social basis of international outcomes. From a modified version of neorealism, this study emphasizes the need to take into account the impact of the structure of the process to the structural change of the system along with opening the first two element of the structure to change by taking into account the principle of segmentation and separateness to functional specification.